The genome sequence of the Black-veined White butterfly, Aporia crataegi (Linnaeus, 1758) [version 2; peer review: 2 approved, 1 not approved] - Sam Ebdon; Alex Hayward; Rebecca Whitla; Saad Arif; Alexander Mackintosh; Konrad Lohse (Wellcome Open Research)
We present a genome assembly from an individual male Aporia crataegi (the black-veined white; Arthropoda; Insecta; Lepidoptera; Pieridae). The genome sequence is 230 megabases in span. The complete assembly is scaffolded into 26 chromosomal pseudomolecules, with the Z sex chromosome assembled. Gene annotation of this assembly on Ensembl has identified 10,860 protein coding genes.